Annual Review of Hydrocephalus 1990
DOI: 10.1007/978-3-662-11152-9_109
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Intraventricular Haemorrhage

Abstract: SummaryThe findings of computerized tomography and clinical features were studied in 19 patients with traumatic intraventricular haemorrhage. Blood was found in various portion of the ventricles. Main sites of the blood was as follows: around the foramen of Monro, 6 patients; in the body and occipital horn of the lateral ventricle, 5 patients; solely in the occipital horn, 8 patients. The haemorrhage around the foramen of Monro, resulting from contusion of the ventral portion of the corpus callosum, septum pel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Piek and Bock described 9 cases of traumatic secondary IVH and reported 2 cases in whom IVH occurred after a lucid interval of 10 hours following injury 12 . Sato et al concluded from their study of 19 patients of traumatic IVH that final outcome of such patients was mainly influenced by the severity of coexisting intracranial lesions 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Piek and Bock described 9 cases of traumatic secondary IVH and reported 2 cases in whom IVH occurred after a lucid interval of 10 hours following injury 12 . Sato et al concluded from their study of 19 patients of traumatic IVH that final outcome of such patients was mainly influenced by the severity of coexisting intracranial lesions 13 .…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] This work proposes that the CT findings listed in Figure 1 are important in terms of intervention, but speculation centers on CT scans that lack these findings. Confirmation that these lesions, in concert with the clinical examination, are therapeutically inconsequential would obviate the need to identify them when they occur in isolation (in the absence of other more serious injuries).…”
Section: Introductionmentioning
confidence: 99%